2013
DOI: 10.1111/wrr.12015
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐7 attenuates TGF‐β1–induced fibroblast‐like differentiation of rat dermal papilla cells

Abstract: Dermal papilla cells (DPCs) show phenotypic plasticity during wound healing. The multipotency of DPCs is well recognized, but the signaling pathways that regulate the differentiation of these cells into fibroblasts are poorly understood. A preliminary experiment showed that transforming growth factor beta1 (TGF-β1) can induce DPCs to differentiate into fibroblast-like cells, which suggests that DPCs may be a source of wound-healing fibroblasts. Bone morphogenetic protein-7 (BMP-7), a member of the TGF-β superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…In the present investigation, we observed that canonical TGF-β signaling suppresses canonical BMP signaling activity in the mesenchymal cells of the posterior palate by competing limited Smad4. The antagonism between TGF-β and BMP signaling has also been reported in several other cells, such as dermal papilla cells, cardiomyocytes and breast cancer cells (Bin et al 2013; Grönroos et al 2012; Wang et al 2012). …”
Section: Discussionmentioning
confidence: 60%
“…In the present investigation, we observed that canonical TGF-β signaling suppresses canonical BMP signaling activity in the mesenchymal cells of the posterior palate by competing limited Smad4. The antagonism between TGF-β and BMP signaling has also been reported in several other cells, such as dermal papilla cells, cardiomyocytes and breast cancer cells (Bin et al 2013; Grönroos et al 2012; Wang et al 2012). …”
Section: Discussionmentioning
confidence: 60%
“…Additionally, the e-CAF compound appears to increase the capacity of myofibroblast replacement, from the reservoir of mesenchymal stem cells that constitute the hair follicle, acquiring a more fibroblast-like phenotype, as it is known to occur in the presence of TGF-β 1 [47,48]; this effect is also enhanced by the employed substrate. In addition, preliminary work on its ability to induce keratinocyte migration and training of ECM was also shown.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, selective affinity of a therapeutic agent for its target kinase is necessary to achieve satisfactory outcomes and avoid side‐effects. For example, in terms of scar formation, the bone morphogenetic protein signalling pathway, which is mediated by other ALKs, has been shown recently to play an antagonistic role against fibroplasia . The ideal anti‐HPS drug should preferably have an affinity with ALK5.…”
Section: Discussionmentioning
confidence: 99%